Evaluación de la eficiencia y calidad de la generación distribuída del campo petrolero Pindo año 2013. propuesta de un programa de mejoras para la generación distribuída. - Chávez Chávez, Romel Patricio (2013)
The present research was done with the objective of to give solutions those allow decrease electricity supply from the distributed generation of the oil field Pindo. At the beginning all the theorical elements are necessary for a right present problematic assimilation and to create the needed bases for its solution, the decline and low quality of the energy given in the industrial nets are addressed, included the main rules considered for the reductions and their control. Immediately a detailed description about the analysis object is done, their components parts and electric supply system, also a detailed about the found problems is done, then the used methodology for the evaluation. Also is included all the mediations done to do the simulations and to adopt the most appropriated variants for the harmonic compensations.